Investment and income effects of land regularization : the case of Nicaragua - Deininger, Klaus W., 1962- 1962- (Policy research working paper, 2002)
In situations where tenure insecurity is pervasive (as in Nicaragua), systematic efforts of land regularization can have positive effects on productivity as well as equity